Endovascular Treatment of Internal Iliac Artery Stenosis in Patients with Buttock Claudication - Prince, Jip F. (Public Library of Science, 2013)
AIM: To assess the technical feasibility and clinical outcome of percutaneous transluminal angioplasty (PTA) with and without stent placement for treatment of buttock claudication caused by internal iliac artery (IIA) stenosis. METHODS: Between September 2001 and July 2011, thirty-four patients with buttock claudication underwent endovascular treatment. After angiographic lesion evaluation PTA with or without stent placement was performed. Technical success was recorded. Clinical outcome post-treatment was assessed at three months post-intervention and was classified as: 1) complete relief of symptoms, 2) partial relief, or 3) no relief of symptoms. Complications during follow-up were recorded. RESULTS: Forty-four lesions in 34 symptomatic patients were treated with PTA. Eight lesions were treated with additional stent placement. Technical success was achieved in 40/44 lesions (91%). Three procedure-related minor complications occurred, i.e. asymptomatic conservatively treated intimal dissections. After a median of 2.9 months, patients experienced no relief of symptoms in 7/34 cases (21%), partial relief in 14/34 cases (41%), and complete relief in 13/34 cases (38%). Six patients required a reintervention during follow-up. CONCLUSION: Endovascular treatment of IIA stenosis has a high technical success rate and a low complication rate. Complete or partial relief of symptoms is achieved in the majority (79%) of patients.